Functional treatment of Condylar Mandibular Process Fractures - Hayder Al khaqani; Ali Abbas Alshawi (Basrah Journal of Surgery, 2023)
Background: Mandibular fracture is one of the commonest facial skeletal injuries, the classical treatment for condylar fracture either by close or open reduction. The purpose of this study is to prove the effectiveness of early functional rehabilitation through the effect of neuromuscular adaptation in unilateral and bilateral condylar fractures . Patients and Methods: A prospective study included thirty patients presenting with condylar fractures, divided into three age groups , group I children less than 12 years old , group II teenagers age range 12-17 years old and group III adult more than 17 years those admitted to maxillofacial department in Al-Basra Teaching Hospital from May,1,2015 until October,30,2016 presented with a malocclusion, a deviated midline, and a limited mouth opening. Computed Tomography is done as early as possible. The method used in our study was the early closed active functional treatment. Results: Young patients less than 12 years of age were 17 (56.7%), also we found that the dislocation of condylar head fracture was more common in the very young age group according to the CT- Scan. Teenagers patients (12-17) years of age were 2 (6.7%) while adult patients more than 17 years old were 11 (36.7%) . Conclusion:The complete condylar remodeling (restitution of condylar head) occurs in very young age group (less than 12 years old) and to less extent in others age groups , the diagnosis depend on ct scan findings in pre and post imaging .